Information security in the Islamic perspective: the principles and practices - Zulhuda, Sonny (Faculty of Science and Technology, UIN Jakarta, 2010)
This paper examines the extent to which Islamic principles and practices (in this respect, as found mainly in the Prophet Muhammad's traditions) reinforce the notion of information security as a measure to protect information assets. This paper is historical and doctrinal in nature, attempting to discover the Islamic formulation that corresponds to the theories and practices of information security as adopted by various industries today. The aim of this paper is to ultimately portray that Islam is indeed a universal and modern religion caring no less about the issues of information security. To achieve this goal, this paper examines how the principles and the practices of information security were recognised and implemented in the early Islamic civilisation. Those practices are further analysed so as to get a more comprehensive view of the criticality of information security to the Muslim society. It restricts its scope to mainly the two fundamental sources of knowledge and laws in Islam, embodied in the holy Qur'anic injunctions and the Prophetic traditions (Hadith) that are of particular relevance.